POST-TRAUMATIC STRESS DISORDER IN KATHLEEN GLASGLOW’S NOVEL GIRL IN PIECES - Malisa Surayya MS; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2022)
This study aims to reveal the Post-Traumatic Stress Disorder in Kathleen Glasgow’s Novel Girl in Pieces. It focuses on the PTSD experienced by the protagonist, Charlie Charlotte Davis. The main purpose of this study is to determine the factors of PTSD and the symptoms of PTSD experienced by Charlie Charlotte Davis. This study applies the theory of PTSD proposed by Rosenberg. In analyzing the topic, the researchers use qualitative research method to process and arranges the data. The types of data of the study are from two data sources, i.e. primary data and secondary data. The primary data are from the text of the novel Girl in Pieces. The researchers find sixteen data to be included in the analysis. The secondary data are taken from books and other sources related to the analysis such as articles on PTSD, literary theory, the author’s biography, internet sites and other relevant information to the analysis of this study. The results of the study show that the factor of PTSD suffered by Charlie are due to psychological factors, such as her beloved father’s death which always makes Charlie remember the sad event, her reminiscences about the past of herself and her beloved late father, which always haunt her that she always blames and harms herself, and always avoids memories that trigger her trauma. She also avoids people’s questions that might make her remember the unpleasant events.